The Effect of Electronic Service Quality and Customer Satisfaction on Customer Purchasing Behavior in Online Pukis Badran Purchases - Tian Alkhana Syaifudin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The expansion of digital commerce has transformed purchasing practices in the food and beverage sector, encouraging businesses to rely increasingly on online sales channels. Within this environment, customers' purchasing decisions are influenced not only by product attributes but also by the quality of electronic services and the satisfaction gained throughout the transaction process. Accordingly, this study investigated the effects of Electronic Service Quality and Customer Satisfaction on Customer Behavior in online purchasing at Pukis Badran, Surakarta. A quantitative associative research design was implemented. The study involved 100 customers who had previously purchased Pukis Badran products through online platforms. Participants were selected using purposive sampling, and primary data were gathered through a structured questionnaire. Data analysis was performed using multiple linear regression with IBM SPSS Statistics. Instrument quality was verified through validity and reliability testing, followed by classical assumption tests before conducting hypothesis testing. The statistical procedures consisted of partial (t-test) and simultaneous (F-test) analyses, together with the coefficient of determination (R²). The analysis revealed that Electronic Service Quality positively affected Customer Behavior (β = 0.254; t = 6.533; p < 0.001). Customer Satisfaction also showed a significant positive relationship with Customer Behavior (β = 0.531; t = 2.737; p = 0.007). Simultaneous testing confirmed that both variables jointly contributed to Customer Behavior (F = 115.769; p < 0.001). Furthermore, the regression model explained 70.5% of the variance in Customer Behavior (R² = 0.705), whereas 29.5% remained attributable to factors outside the proposed model. These findings indicate that strengthening electronic service quality alongside maintaining customer satisfaction is essential for fostering positive customer behavior in online purchasing.